Republic of the Philippines Review of the Social Security System : Considerations for Strengthening Sustainability and Coverage - World Bank (Washington, DC, 2016)
This report was prepared at the request of the Philippines Social Security System (SSS) to analyze key challenges and propose reform options to improve the sustainability and expand the coverage of old age income protection for private sector workers. A simulation employing the Pension Reform Options Simulation Toolkit (PROST) found that the SSS scheme will face outflows greater than inflows in about 20 years and depletion of its assets in about 28 years. Fortunately, its medium-term financing issues can be addressed through the gradual introduction of parametric reforms that shield workers and retirees from abrupt changes in contributions and benefits. At the same time, the Philippines faces a challenge to improve the defacto coverage of workers by Social Security, and to increase the income protection coverage of the elderly. Options suggested include SSS measures to leverage its identification system and introduce a special instrument for informal workers. Rather than introducing matching contribution subsidies to expand coverage, it was suggested to broaden the scope of beneficiaries eligible for social pensions. Beyond the scope of the SSS, additional measures were suggested including those to improve the access and efficiency of contributions and payments systems, strengthening mobile-money platforms and efforts to improve access to savings instruments, particularly for small and isolated savers. The report points out that the key means of improving coverage lies beyond the scope of social security or pensions, namely, to improve the quantity and quality of wage-based employment.